Improved lymphatic targeting: effect and mechanism of synthetic borneol on lymph node uptake of 7-ethyl-10-hydroxycamptothecin nanoliposomes following subcutaneous administration - Tiantian Ye; Yue Wu; Lei Shang; Xueqing Deng; Shujun Wang (Taylor & Francis Group, 2018)
Borneol as a penetration enhancer is widely used in guiding other components through the biological barrier into the targeting organs or tissues. This study aimed at studying effect and mechanism of synthetic borneol (S-BO) on improving lymphatic-targeting ability of 7-ethyl-10-hydroxycamptothecin liposomes (SN-38-Lips) via increasing lymph node uptake. At first, SN-38-Lips prepared had appropriate particle distribution, drug loading property and compatible stability with S-BO. Both in vitro cellular uptake and in vivo fluorescence imaging showed that 2 and 5 mg/mL S-BO, especially 2 mg/mL S-BO, enhanced cytoplasmic fluorescence signal of SN-38-Lips in the macrophages based on phagocytosis effect. And high-intensity zone appeared in the paracortex and medulla of popliteal lymph node. SN-38-Lips were subcutaneously (s.c.) injected into the right footpad of KM rats in the dose of 4 mg/kg following s.c. injection of 1, 2 and 5 mg/mL BO suspension. The lymphatic pharmacokinetics were investigated to explore the promotion law of S-BO, and combined with tissue irritation to optimize S-BO concentrations. The results indicated that 2 mg/mL S-BO could reduce injection-site retention, and prolong residence time and increase uptake of lymph nodes, which would not cause inflammatory reaction of injection site. In conclusion, the present study may provide a basic study for improving lymphatic-targeting ability of SN-38-Lips by the S-BO regulation, and to be the helpful guidance for further study in lymphatic targeting of delivery system.